Analisis Ground Shear Strain HVSR untuk Mengidentifikasi Potensi Gerakan Tanah di Kecamatan Kadia, Kota Kendari - Kristiani Eka Ratte; Abdul Manan; Laode Ihksan Juarzan (Program Studi Teknik Geofisika FITK UHO, 2024)
This research on Ground Shear Strain (GSS) was carried out to determine the potential for ground movements in Kadia District, Kendari City. In its implementation, GSS is processed using microtremor data from measurements in the field. GSS is the result of multiplying the Seismic Vulnerability Index (Kg) and the basement Peak Ground Acceleration (PGA). Microtremor data were taken at 16 measurement points with a distance between measurement points of 400 to 600 m. The microtremor data were then analyzed using the HVSR (Horizontal to Vertical Spectral Ratio) method available in Geopsy 3.3.6 software to obtain predominant frequency values (fo) and amplification factors (Ao). These two parameters are used to calculate the Kg value. The PGA value is determined using the Fukushima and Tanaka empirical formula using earthquake data with a depth of ≤ 50 km and surface magnitude (MS) ≥ 5 SR. The research results show that the GSS values in Kadia District, Kendari City ranges from 1.1768x10-4 to 6.5436x10-4. Based on the results of ground movement analysis, it is known that Kadia District, Kendari City, has the potential to experience cracks or land subsidence if an earthquake occurs with elasto-plastic soil dynamics. Apart from that, it is also known that the Kadia District area of Kendari City is not prone to landslides and liquefaction because g < 10-2.